Decoloniality in physiotherapy education, research and practice in South Africa - Saul Cobbing (South African Journal of Physiotherapy, 2021)
Background: Historically, the profession of physiotherapy in South Africa has closely aligned itself with our former colonial master, the United Kingdom. Whilst efforts have been made in recent years to transform our profession, numerous challenges remain. An improved understanding of the topic of decoloniality is a useful and necessary way of beginning to address these challenges.